Effects of single-stage syngas hydrotreating on the physical and chemical properties of oxidized fractionated bio-oil. (1st December 2017) - Luo, Yan; Hassan, El Barbary; Miao, Peng; Xu, Quan; Steele, Philip H.
Abstract: Previous research has shown that syngas can successfully hydrotreat bio-oil, but the hydrotreated products still had high viscosity, total acid number, oxygen content, etc. The current study was based on the hypothesis that higher temperature syngas hydrotreating may reduce the viscosity, total acid number, oxygen content and increase the total hydrocarbon concentration. In the current study, hydrotreating of oxidized fractionated bio-oil was performed at 400 °C in the presence of syngas (molar ratio H2 : CO was 4:6). The total yield of the organic liquid product was 34.2 wt%, and 40 wt% of the total organic phase was composed of hydrocarbons (olefins, aromatics and polyaromatics). The treated bio-oil had upgraded physiochemical properties with a water content of 1.6 vol%, a higher heating value of 38.3 MJ/kg, a density of 0.96 g/mL, a viscosity of 12.2 cSt and a total acid number of 22.0 mg KOH/g. Functional group distinctions were detected by Fourier transform infrared spectroscopy and the chemical composition differences were identified by gas chromatography/mass spectrometry. The results indicated that the fractionated bio-oil had been greatly improved by syngas hydrotreating at 400 °C. This success of syngas hydrotreating at a higher temperature has the potential to allow the replacement of hydrogen with syngas for the partial upgrading of oxidized bio-oil.